Sociocultural and historical contexts of African American English - Lanehart, Sonja L. (Varieties of English around the world. General series, 2001)
This volume, based on presentations at a 1998 state of the art conference at the University of Georgia, critically examines African American English (AAE) socially, culturally, historically, and educationally. It explores the relationship between AAE and other varieties of English (namely Southern White Vernaculars, Gullah, and Caribbean English creoles), language use in the African American community (e.g., Hip Hop, women's language, and directness), and application of our knowledge about AAE to issues in education (e.g., improving overall academic success). To its credit (since most books av.